Wind Regulation of Emergence Times and Early Larval Survival in Capelin ( Mallotus villosus) - Frank, Kenneth T.; Leggett, William C. (Canadian Journal of Fisheries and Aquatic Sciences, 1981)
Factors regulating the emergence and survival of capelin (Mallotus villosus) larvae from their beach gravel nest sites were investigated in the spring and summer of 1978 and 1979. In both years, the pattern of larval emergence was characterized by intermittent abrupt increases in the numbers of larvae in the nearshore waters and corresponding precipitous declines in the density of preemergent larvae in the beach gravel. Both events were strongly correlated with onshore wind-induced wave action which disturbed the beach. Larval emergence patterns were unrelated to changes in tidal amplitude or day–night variation. The generality of this wind-induced larval emergence hypothesis was tested and confirmed using published data from two separate studies conducted at three different Newfoundland sites during 1927, 1929, 1930, and 1941. The density of larvae in the beach gravel was positively correlated with the length of time separating the occurrence of onshore winds. The result was a pronounced temporal clumping of larvae hatching at different times, periodic releases of large numbers of larvae into the aquatic environment, and a progressive deterioration in the physical condition of larvae emerging as beach residence time increased. The frequency of onshore winds during the hatching period was 50% greater in 1979 relative to 1978. Egg densities were similar in 1978 and 1979 but larval densities (no./m 3 ) in the nearshore environment were 60% greater in 1979. This increase in larval density conformed to the increase in the proportion of larvae exiting the beach in good physical condition in 1979.Key words: capelin, Mallotus villosus; Newfoundland, larval emergence, larval survival, wind, population biology, beach spawning, coastal environments, year-class strength